Quality of Life and characterization of patients with atopic dermatitis in Portugal - QUADEP study - Carvalho, D (2019)
OBJECTIVES: To investigate the quality of life (QoL) and to characterize patients with atopic dermatitis (AD) in Portugal. METHODS: This was a cross-sectional study, including patients with AD and other eczemas. Skindex-29, Skindex-teen and Childhood Atopic Dermatitis Impact Scale (CADIS) were the instruments used to assess QoL in adults, teenagers, and children respectively. Complementarily, the SF-12 was used and disease severity was evaluated through Patient-Oriented SCORAD (PO-SCORAD). Odds Ratio (OR) were performed to measure associations with QoL. SPSS statistics 95% confidence intervals and values of p<0.05 were considered statistically significant. RESULTS: 162 participants were included, aging 0.5-74 years. We found that 37.3% of AD patients consider their disease as disabling and more than half of AD patients feel stigmatized by society. The mean Skindex score for AD was 39.68, and 44% patients presented a severe QoL impact. "Symptoms" was the most affected category in adults. Moderate to severe AD patients were 87% of the sample. Regarding the factors that most influenced worse QoL in AD, with increasing age, the Skindex score is likely to increase (OR: 1.03 [95%CI 1.00-1.06]). "Consider having disability" was also associated, OR: 6.72 (95%CI 2.56-17.63). With increasing affected body area and edema, the QoL worsens (OR: 1.07 [95%CI 1.03-1.11] and OR: 2.04 [95%CI 1.23-3.40], respectively). CONCLUSIONS: This is the first study with QoL data about AD patients in Portugal, revealing an expected negative impact. More awareness-raising activities are needed to increase literacy, decrease the stigma, and consequently to address some impacted factors in AD patients' QoL.